The Fantasy Formula in Rise of the Guardians (2012) Movie by Peter Ramsey - Sofyan Kurniawan; Rahmawati Azi; Nur Israfyan Sofian (ELITE: Journal of English Language and Literature, 2025)
Heroes do not always have to be perfect; they can also have flaws that then become their strengths. This research discusses the conventions and inventions of fantasy formula in the movie Rise of the Guardians (2012), focusing on the hero, the other, helpers and guides, the call, the journey, the treasure, and the transformation. The research method employed is a descriptive qualitative approach. The research reveals that the movie incorporates both convention and invention in its fantasy formula. The conventions are: 1) The 'the other' character is Pitch. Howard is depicted with a pale face and is always seen wearing black clothes. 2) The ‘the wise old man’ character is Man in the Moon. Howard provides guidance to the heroes in the form of advice. 3) The ‘treasure’ is the return of the children's belief in the guardians. According to Howard, treasures are sometimes intangible. 4) The ‘transformation’, by Howard, after getting the treasure, and after fighting alongside the other guardians, Jack turns into the hero he should be. While the inventions are: 1) ‘The hero’, not by Howard, the heroes in the movie are not desperately unhappy and experience their lives as a stultifying world. 2) ‘The call’, not by Howard, Jack receives the call but lacks insight, courage, or endurance. 3) ‘The Journey’, not by Howard, the heroes do not leave the original world nor cross over to a mysterious one.